Type III Vasa Previa Associated with Resolution of a Low-Lying Placenta: Case Report and Literature Review - Kim, Joanna J.; Bonhomme, Katherine; Oppenheimer, Lawrence W.; Gaudet, Laura (American Journal of Perinatology Reports, 2024)
Vasa previa occurs when fetal vessels lie above the cervical os. A novel type of vasa previa, known as type III, is characterized by an abnormal branching of fetal vessels from the placenta in the absence of velamentous cord insertion (as seen in type I) or multilobed placenta (as seen in type II). Here, we present a case of a type III vasa previa after a resolution of a low-lying placenta. The presence of any known risk factors of vasa previa, including low-lying placenta, should prompt screening for vasa previa in the third trimester. Accurate and timely diagnosis of vasa previa will confer significant survival benefit for the neonate.
Keywords: vasa previa; placenta; prenatal diagnosis; fetal medicine